Development of Masterplan and Initial Program for Food Security in Papua Region, Indonesia - Ambar Pertiwiningrum; Cahyono Agus; Supriadi Supriadi; Supriyanta Supriyanta; Ali Agus; Richard P Napitupulu; Yudistira Soeherman (Department of Urban and Regional Planning, Diponegoro University, 2018)
Food Security and Vulnerability Atlas (FSVA) of Indonesia 2015 categorized the vulnerability to food and nutrition insecurity based on nine indicators covering food availability, food access and food utilization. According to the assessment, 14 districts in priority 1 (severely vulnerable to food insecurity) were all in Papua. Responding to the problems of food insecurity, a multi-year program focusing on two regencies, i.e., Manokwari and Merauke, was conducted from August 2015. The program was developed in cooperation with the Ministry of Villages, Disadvantaged Regions and Transmigration (Kemendes PDTT), Gadjah Mada University Yogyakarta and district governments. This research aimed to examine the problems causing food insecurity and to develop integrative and collaborative macro-scale policy recommendations. The study used a qualitative descriptive method and a pilot project approach to address food insecurity problems in both regencies. It found five main issues related to food insecurity in Papua: the prevalence of stunting among children under five, the ratio of per capita normative consumption towards net cereal production, the population living below poverty line, households without access to clean water, and low-income families. The problems could be overcome by concerning the ratio of normative consumption per capita and the preservation of local food, and local crops should be grown especially tubers. Regarding the problems associated with low-income families, a program that should be implemented is the welfare improvement of the rural low-income families through the optimization of land resources in the integrated and intensive ways in response to many land resources still underutilized. Moreover, water treatment should be encouraged further to tackle clean water issues.